Embedding occupational health and safety in the procurement and management of infrastructure projects: institutional logics at play in the context of new public management. Issue 10 (3rd October 2019) - Lingard, Helen; Oswald, David; Le, Tiendung
Abstract: The research explored the approaches used by government agencies (as client organizations) to drive occupational health and safety (OHS) performance improvements in publicly funded infrastructure construction projects in Australia. Semi-structured interviews were conducted with 32 representatives of clients and contractors with direct and recent experience of delivering large public infrastructure projects. Interviews explored the procurement approaches taken, and the use of incentives and performance measurement. Data was subjected to inductive analysis to identify emergent concepts and themes relating to the way that New Public Management (NPM) influences the commercial management of infrastructure construction projects, with particular reference to OHS impacts. The concept of institutional logics was utilised as a theoretical frame to understand clients' behaviour in the commercial management of infrastructure projects. Client behaviour was consistent with elements of NPM and reflected a managerialist logic in the pursuit of efficiency, the use of targets, incentives and performance measurement. However, a strong professional service logic was also found to drive active client behaviour in relation to the management of OHS. Understanding the institutional logics driving client OHS practices is an important theoretical development that can stimulate reflexive practice which may create an impetus for change.